2017
DOI: 10.1016/j.ophtha.2017.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Predictors of Risk for Progression to Non-Neovascular Atrophic Age-Related Macular Degeneration

Abstract: Purpose The appearance of geographic atrophy (GA) on color photography (CP) is preceded by specific features on spectral domain optical coherence tomography (SDOCT). We aimed to build SDOCT-based risk assessment models for 5-year new onset of GA and central GA on CP. Design Prospective longitudinal study. Participants Age-related macular degeneration (AMD) patients with bilateral large drusen and/or non-central GA, and at least one eye without advanced disease (n=317) enrolled in the multicenter Age-Relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 54 publications
2
55
1
2
Order By: Relevance
“…Persistent BLamD has been erroneously considered the outer plexiform layer by some authors, possibly contributing to a false impression of viable photoreceptors in atrophic areas. 89,90 Thus, we encourage developers of automated OCT segmentation strategies 91 and nomenclatures 92,93 to incorporate the presence of BLamD, especially in atrophy. Further, because the fourth hyper-reflective outer retinal band of the consensus lexicon correlates to the RPE-BL-BrM complex 94 (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent BLamD has been erroneously considered the outer plexiform layer by some authors, possibly contributing to a false impression of viable photoreceptors in atrophic areas. 89,90 Thus, we encourage developers of automated OCT segmentation strategies 91 and nomenclatures 92,93 to incorporate the presence of BLamD, especially in atrophy. Further, because the fourth hyper-reflective outer retinal band of the consensus lexicon correlates to the RPE-BL-BrM complex 94 (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are also consistent with studies using SD-OCT imaging, in which soft drusen in macaques demonstrate homogenous internal reflectivity, whereas those in humans exhibit greater heterogeneity in reflectivity with variable internal substructures. 8,58,59 Thus our data suggests both localized and global impact on lipofuscin distribution in eyes with drusen and AMD in primate species. As the pathogenesis of AMD is complex and multifactorial, including oxidative stress, 60 lipid accumulation, 61,62 immune dysregulation, 63,64 and vascular changes, 65,66 the role of lipofuscin accumulation among these factors remains unclear.…”
Section: Discussionmentioning
confidence: 53%
“…SD-OCT can quantify variation in morphology in a way that is accurate and reproducible. Other AMD phenotypes detectable on OCT including subfoveal fluid, retinal and choroidal thickness, retinal hyperreflective foci, other drusen characteristics such as hyper-reflectivity and homogeneity, are opportunities for exploration in the context of subtyping AMD and assessing risk of progression, 15,16,23,48 as well as defining the associations with genetic variants.…”
Section: Resultsmentioning
confidence: 99%
“…14 Sleiman et al demonstrated that OCT based drusen measurements were associated with appearance of geographic atrophy on color photographs over 4 years. 48 Schmidt-Erfurth et al found that drusen area was an important quatitative feature for progression. 16 Higher drusen volume was related to advanced AMD in a retrospective review by Lei et al, but other OCT parameters were more strongly related in their cases.…”
Section: Discussionmentioning
confidence: 99%